Characterization of Natural Killer Cells and Cytokines in Maternal Placenta and Fetus of Diabetic Mothers - Cristiane de Castro Pernet Hara; Eduardo Luzía França; Danny Laura Gomes Fagundes; Adriele Ataides de Queiroz; Marilza Vieira Cunha Rudge; Adenilda Cristina Honorio-França; Iracema de Mattos Paranhos Calderon (Journal of Immunology Research)
The present study characterized natural killer cells and cytokines in diabetic mothers, their placenta, and fetus. In the maternal blood from the hyperglycemic groups, the CD16+CD56− NK cells increased, whereas that of CD16+CD56+ decreased in gestational diabetes mellitus [GDM] group. Cord blood from type 2 diabetes [DM-2] showed a higher proportion of CD16+CD56− and CD16−CD56+. The placental extravillous layer of GDM and DM-2 showed an increase of CD16+CD56− cells and, irrespective of region, the proportion of CD16−CD56+ cells was higher in mild gestational hyperglycemia [MGH] and GDM and lower in DM-2. IL-2 was lower in maternal blood and IFN-γ higher in maternal and cord blood from the GDM group. IL-17 was higher in maternal and cord blood from the DM-2 group. The placental extravillous layer of the MGH showed high levels of IL-4, IL-6, IL-10, IL-17, and IFN-γ and low levels of IL-1β and IL-8, whereas the placental villous layer contained high levels of IL-17 and IFN-γ. The GDM group, irrespective of region, showed higher levels of IL-8. The DM-2 group, irrespective of region, placenta showed high levels of TNF-α, IL-17, and IFN-γ. The hyperglycemia produces an inflammatory environment with a high content of inflammatory cytokines and cells expressing CD16+.